PROBLEMS OF ARTIFICIAL INTELLIGENCE IN ECOLOGICAL FORECASTING - Nesterov I.I.; Kozhevnikov Y.A.; Ryadinskii V.Y. (My University, 2007)
Two multidisciplinary problems exist in the field of ecological forecasting: (i) measurements in soil, air, and water; (ii) interpretation of these measurements for forecasting or making administrative decisions about industrial activity. The main issue in the solution to the first problem is realization of the object of research (scope of measured properties, establishment of scales, and accuracy of measurements) at present and development of theoretical ecology in the future. The main difficulty in the solution to the second problem is the choice and use of mathematical methods applicable to the problems and quality of measurements.